2021
DOI: 10.3390/ijerph18042125
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Phthalate and Organophosphate Esters via Indoor Dust and PM10 Is a Cause of Concern for the Exposed Saudi Population

Abstract: In this study, we measured the occurrence of organophosphate esters (OPEs) and phthalates in the settled dust (floor and air conditioner filter dust) and in suspended particulate matter (PM10) from different microenvironments (households (n = 20), offices (n = 10) and hotels (n = 10)) of Jeddah, Saudi Arabia. Bis (2-Ethylhexyl) phthalate (DEHP) was the major pollutant (contributing > 85% of total chemicals burden) in all types of indoor dust with a concentration up to 3,901,500 ng g−1. While dibutyl phthala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…High levels of EDIs for children were found in populations in Saudi Arabia [ 29 ], Brazil [ 1 ] and South Africa [ 66 ] than in other studied children. Especially, the median EDI of TDCPP, which is the most important contributor for total EDIs of OPEs, is significantly higher than that of TPHP for each population in Saudi Arabia and Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of EDIs for children were found in populations in Saudi Arabia [ 29 ], Brazil [ 1 ] and South Africa [ 66 ] than in other studied children. Especially, the median EDI of TDCPP, which is the most important contributor for total EDIs of OPEs, is significantly higher than that of TPHP for each population in Saudi Arabia and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…For the results of risk assessment, we compared the results of this study with those previously reported. In the Saudi Arabia study, EDI was multifold below RfD values for TDCPP and TPHP for exposure from dust [ 29 ]. However, estimated incremental lifetime cancer risk (ILCR) with moderate risk (1.5 × 10 −5 ) for Saudi adults and calculated hazardous index (HI) of >1 for Saudi children from bis(2-ethylhexyl) phthalate (DEHP) showed a cause of concern to local public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some toxicological studies have found that TCEP and TEHP have carcinogenic potential and indoor dusts vary according to the indoor environments studied [56][57][58] . ILCR values were estimated in the three cities and for the different age groups [Table 3, Figure 4].…”
Section: Human Exposure Assessmentmentioning
confidence: 99%
“…Soil and river sediment samples collected from Tianjin, China and Bagmati River, Nepal showed 37.7 to 2100 ng/g and 983 to 7660 ng/g of OPFRs [ 8 , 9 ]. Persistent use of OPFRs in consumer products and their appearance in environmental samples raises concerns for human exposure via the consumption of drinking water, inhalation of indoor dust, and absorption of contaminated food [ 10 ]. Human biomonitoring studies have also confirmed the presence of OPFRs in human body fluids [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%